The dilemma between acid and base catalysis in the synthesis of benzimidazole from o-phenylenediamine and carbon dioxide. Issue 87 (14th October 2019) - Hulla, Martin; Nussbaum, Simon; Bonnin, Alexy R.; Dyson, Paul J.
Abstract : Synthesis of azoles from ortho -substituted anilines and CO2 is limited by the cyclization reaction and not by CO2 reduction. Abstract : The tandem synthesis of benzimidazole and other azoles can be achived by the N -formylation of ortho -substituted anilines followed by a cyclization reaction. However, CO2 -based N -formylations with hydrosilane reducing agents are base catalyzed whereas the cyclization reaction is acid catalyzed. The mismatch in catalytic conditions means that only one of the steps can be catalyzed in a single pot reaction. While the N -formylation reaction is frequently the target of catalyst development, the cyclization reaction requires comparably much harsher reaction conditions. Identification of these difficulties lead us to the development of a one-pot, two-step synthesis of benzimidazole under mild reaction conditions employing acid catalysts.